Does Social Trust Influence Charitable Giving for NGOs? - Halina Waniak‑Michalak; Ivana Perica (Comparative Economic Research. Central and Eastern Europe, 2021)
The purpose of the paper is to find a link between the level of NGOs' revenues and the trust in non-governmental organisations (NGOs). We investigate if social trust, as measured by the Charities Aid Foundation, influences their charitable revenues. We analyse the revenues of NGOs in three countries: Poland, Croatia and the United Kingdom. We analyse the change in social trust in these countries and revenues in the years 2013-2017. The design and methodology approach includes a literature review and panel regression analysis. The main results of the panel regression analysis indicate that the amount of donations depends not only on the level of public trust but also on certain external and independent factors. We find that NGOs revenues vary from country to country due to different levels of economic development and wealth of countries. The results also show that apart from demographics, NGOs' revenues and the donations they receive are also influenced by the philanthropic goal, the numer of years since it was established (the age of the organization) and the financing model. The research limitations include the selection of only a few countries for the analysis. This paper's originality and value lie in the fact that the problem of low social trust in NGOs is analysed by linking it with the NGOs' revenues.
Keywords: 330; NGOs; civil trust; revenues; donations